Orienting Negative Politeness Strategies Towards the Hearer Negative Face in Disney’s Frozen Movie - Putu Ayu Anggita Gangga Swari; I Made Netra; Ketut Santi Indriani (VISA: Journal of Vision and Ideas, 2024)
The study aims to analyze the use of negative politeness strategies by characters in Disney's “Frozen” movie using Brown and Levinson's (1987) politeness theory, focusing on how these strategies address the hearer's negative face. The data of the research were taken from Disney's "Frozen” movie script and analyzed with the theory proposed by Brown and Levinson (1987). Data were collected using the documentation method and note-taking technique. Additionally, to analyze the data, descriptive qualitative methods were used. The results discovered in this research are; be conventionally indirect 9 times, question and hedge 4 times, be pessimistic 5 times, minimize the imposition 12 times, give deference 13 times, apologize 8 times, impersonalize speaker and hearer 16 times, and go on record as incurring debt or not indebting 1 time. The findings contribute to a deeper understanding of how negative politeness works in the “Frozen” storyline and its implications for the interpersonal communication dynamics depicted in the movie.